Layer-by-layer (chitosan/polystyrene sulfonate) membrane-based fabry–perot interferometric fiber optic biosensor - Chen, Li Han (2013)
A label-free, layer-by-layer (LBL) modified, fiberoptic interferometry biosensor for real-time affinity-based protein sensing applications has been proposed. The proposed sensor allows real-time protein adsorption detection by monitoring interference wavelength shifts, which offers better dynamic range and stability in comparison to current detection of changes in optical intensity. With a label-free sensing mechanism, it eliminates issues of progressive leaching of indicators, expensive and time-consuming labeling procedures and undesirable nonspecific interactions with target proteins. The unique Fabry-Perot cavity consists of an LBL coating layer of nanometre thickness deposited on the distal ends of a hollow core cavity spliced to a standard single-mode optical fiber (SMF). This novel configuration allows the LBL sensing element to be enclosed by similar mediums, on both sides of the LBL multilayer film coat, thus surrounded by identical properties such as the same refractive index that improves the sensitivity of the proposed sensor. Furthermore, the LBL coat consisting of chitosan and polysodium styrene sulfonate, commonly used in drug delivery and cell culture, indicates good biocompatibility for future in vivo biomedical applications such as immunosensing and DNA hybridization detections.